Lentil adaptation to drought stress: response, tolerance, and breeding approaches - Noor, Md. Mahmud Al; Tahjib-Ul-Arif, Md.; Alim, S. M. Abdul; Islam, Md. Mohimenul; Hasan, Md. Toufiq; Babar, Md. Ali; Hossain, Mohammad Anwar; Jewel, Zilhas Ahmed; Murata, Yoshiyuki; Mostofa, Mohammad Golam (Frontiers in Plant Science, 2024)
Lentil (Lens culinaris Medik.) is a cool season legume crop that plays vital roles in food and nutritional security, mostly in least developed countries. Lentils are often cultivated in dry and semidry regions, where the primary abiotic factor is drought stress which negatively impacts lentil growth and development, resulting in a reduction of plant production. To withstand against drought-induced multiple negative effects, lentil plants evolved a variety of adaptation strategies that can be classified within three broad categories of drought tolerance mechanisms (i.e., escape, avoidance, and tolerance). Lentil adapts to drought by the modulation of various traits in the root system, leaf architecture, canopy structure, branching, anatomical features, and flowering process. Furthermore, the activation of certain defensive biochemical pathways as well as genes or transcriptional factors are linked to lentil drought tolerance. Plant breeders are continuously working by employing conventional and mutation breeding approaches to develop lentil varieties that can withstand drought, however, little progress has been made in developing drought-tolerant lentil using genomics-assisted technologies. This review summarizes the current understanding on the morpho-physiological, biochemical, and molecular mechanisms of lentil adaptation to drought stress. It also explored how omics-assisted breeding approaches can be utilized to develop lentil varieties that are resilient to drought stress.